2^2m-1*16*8^m-1+(-4^m)*8^m
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 22:34:55
2^2m-1*16*8^m-1+(-4^m)*8^m2^2m-1*16*8^m-1+(-4^m)*8^m2^2m-1*16*8^m-1+(-4^m)*8^m2^(2m-1)*2^4*2^3(m-1)-
2^2m-1*16*8^m-1+(-4^m)*8^m
2^2m-1*16*8^m-1+(-4^m)*8^m
2^2m-1*16*8^m-1+(-4^m)*8^m
2^(2m-1)*2^4*2^3(m-1)-2^2m*2^3m
=2^(2m-1+4+3m-3)-2^(2m+3m)
=2^5m-2^5m
=0
2^(2m-1)*16*8^(m-1)+(-4^m)*8^m
=2^(2m-1)*2^4*(2^3)^(m-1)-4^m*(2^3)^m
=2^(2m-1)*2^4*2^[3(m-1)]-(2^2)^m*2^(3m)
=2^(2m-1)*2^4*2^(3m-3)-2^(2m)*2^(3m)
=2^[(2m-1)+4+(3m-3)]-2^(2m+3m)
=2^(5m)-2^(5m)
=0.
2^2m-1*16*8^m-1+(-4^m)*8^m(m为正整数)
已知m>4,化简|m-4|+|7-2m|+|m×m-2m+1|-|m×m-2m-3|
2^2m-1*16*8^m-1+(-4^m)*8^m
2^(2m-1)×16×8^(m-1)+(-4^m)×8^mRT,2^(2m-1)×16×8^(m-1)+(-4^m)×8^m
当m=1/2时,求15m²-9-{-4m²+[5m-8m²-(2m²-m)+9m²]-3m}
已知2^m=a,化简16×2^2m-1 ×2^3m-1 -4^m ×8^m
已知2^m=a,化简16×2^2m-1 ×2^3m-1 -4^m ×8^m
4m(m的平方-2m-1)+m(2m+5)(5-2m)
m*m-2m等于1,则2m*m-4m+2012
化简求值 m-4/m^2-9(1加上 14m-7/m^2+8m+16)÷1/m-3 其中m=5化简求值:(m-4)/(m^2-9)•{1+[(14m-7)/(m^2+8m+16)]}÷[1/(m-3) ]其中m=5
化简求值m-4/m^2-9(1加上 14m-7/m^2-8m+16)÷1/m-3 其中m=5化简求值m-4/m^2-9(1加上 14m-7/m^2-8m+16)÷1/m-3 其中m=5
m*m-5m-1=0则2m*m-5m+1/m*m
已知m*m+m-1=0,求m*m*m+2m*m-2005
计算:16-m^2/16+8m+m^2÷m-4/2m+8×m-2/m+2
已知m>4,化简:|m-4|+|7-2m|+|m^2-2m+1|-|m^2-2m-3|
化简,:3(m-1)^2+(m+2)(m^2-2m+4)-m(m^2+3m-3)
计算2m+6/m²-4m+4·1/m+3·(m-2)(m+3)/m+3
m-2m-3m+4m-5m-6m+7m-8m-9m+...+2002m-2003m-2004m求m的值